Socio-racial discrimination and racism in Peruvian education A sight from teachers in Lima - Jacinto Pazos, Pedro (2017)
Teachers and students, are a pretext as a specific case, but also as a symbolic case, but at the same time can be the racial and racist imaginary Peru today at school. This bearing in mind, that is the state or the government directs, while noting that are their subjective and meaningful standards that describe. Here, our - reflective empirical contribution is manifested in the knowledge that we elaborate on the different behaviors and behaviors that are established at school level , from social actors that They run. And about all, this perception of socio - racial, and different areas of the idea of racist discrimination are demonstrated.